Computer-controlled submillimeter Fourier spectrometer - VIJ, JAGDISH KUMAR (IEEE, 1989)
A system for a submillimeter wave Fourier transform spectroscopy (FTS) has been automated for the measurement of the power absorption coefficient of liquids in the wavenumber range 10- 400 cm-?. The interferometer is interfaced with a RM380Z Research Machines microcomputer. Software and hardware have been developed to automate the process of collecting and storing the data. Some points of relevance to the analysis of interferometric data are reviewed including the use of phase modulation, the resolution of spectra computed using the discrete Fourier transform, and the necessity of proper optical filtering in spectrometers which use Fourier transform techniques. Spectra measured using the FTS system described here have been compared with results obtained recently using a tunable submillimeter laser and a good agreement is found between the two sets of data.
PUBLISHED
Keywords: Electronic & Electrical Engineering